Push and Pull factors of migration amongst livestock rearers distressed by national calamity in India: A Polytomous Universal Model analysis - LAL, SUDHANAND PRASAD; KADIAN, K S; WODAJO, WORKNEH ABEBE (The Indian Journal of Animal Sciences, 2017)
An endeavor was made to figure out push and pull factors of migration amongst livestock rearers distressed by national calamity in India. Reckoning ordinal response of 160 respondents; 86, 38 and 36 respondents were classified as not-adopter, partially adopter and fully adopter of migration, respectively; subsequently coding it into 0, 1 and 2 for the final Polytomous Universal Model (PLUM). Triangulation of different tests was done to justify aptness of PLUM. Predictor variables viz. age, income, livestock-holding [odds ratio (OR), 0.638; 99% CI of Estimate (E) =-.799 to -.101] and skilled work was statistically significant at 1% level but age and livestock-holding was found to be negatively significant. However, remaining 2 explanatory variables viz. expectation level and land holdings increased the probability for migration among farmers. Major push factor of migration was non-availability of work during agricultural lean season and pull factor was expectation of higher income. This plausibly signifies that, if curbing migration from rural to urban region is a policy agenda of government, variables identified through PLUM, viz. age, income, livestock-holding and skilled work should be given due consideration. The researchers conclude that the identified predictive variables could become cornerstone for migratory research work among livestock rearers, as such an investigation is scarce in India and worldwide.